High-Voltage AlGaN/GaN-Based Lateral Schottky Barrier Diodes - 康贺 王权 肖红领 王翠梅 姜丽娟 冯舂 陈竑 殷海波 王晓亮 王占国 侯洵 (Chinese physics letters, 2014)
Lateral Schottky barrier diodes （SBDs） on A1GaN/GaN heterojunctions are fabricated and studied. The characteristics of the fabricated SBDs with different Schottky contact diameters and different Schottky-Ohmic contact spacings are investigated. The breakdown voltage can be increased by either increasing the Schottky-Ohmie con- tact spacing or increasing the Schottky contact diameter. However, the specific on-resistance is increased at the same time. A high breakdown voltage of 1400 V and low reverse leakage current below 20nA are achieved by the device with a Schottky contact diameter of 100 μm and a contact spacing of 40 μm, yielding a high V^2BR/ RoN,sp value of 194 MW.cm^-2.